A Pacific needs analysis model: a proposed methodology for assessing the needs of facility-based emergency care in the Pacific region - Georgina Phillips; Kathryn Bowman; Trina Sale; Gerard O'Reilly (BMC, 2020)
Abstract Background Emergency care (EC) describes team-based, multidisciplinary clinical service provision, advocacy and health systems strengthening to address all urgent aspects of illness and injury for all people. In order to improve facility-based EC delivery, a structured framework is necessary to outline current capacity and future needs. This paper draws on examples of EC Needs Assessments performed at the national hospitals of three different Pacific Island Countries (PICs), to describe the development, implementation and validation of a structured assessment tool and methodological approach to conducting an EC Needs Assessment in the Pacific region. Methods This is a retrospective, descriptive analysis of the development of the Pacific Emergency Care Assessment (PECA) table using patient-focused principles within an EC systems framework. Tool implementation occurred through observation, literature review and interviews using a strengths-based, action-research and ethnographic methodological approach in Timor-Leste, Kiribati and the Solomon Islands. The 2014 Solomon Islands EC Needs Assessment provides the main context to illustrate and discuss the overall conduct, feasibility, validity and reliability of the PECA tool and methodological approach. Results In each site, the methodological implementation enabled completion of both the PECA table and comprehensive report within approximately 6 weeks of first arriving in country. Reports synthesising findings, recommendations, priority action areas and strategies were distributed widely amongst stakeholders. Examples illustrate Face and Content, Construct and Catalytic validity, including subsequent process and infrastructure improvements triggered by the EC Needs Assessment in each site. Triangulation of information and consistency of use over time enhanced reliability of the PECA tool. Compared to other EC assessment models, the Pacific approach enabled rich data on capacity and real-life function of EC facilities. The qualitative, strengths-based method engenders long-term partnerships and positive action, but takes time and requires tailoring to a specific site. Conclusion In PICs and other global contexts where EC resources are underdeveloped, a PECA-style approach to conducting an EC Needs Assessment can trigger positive change through high local stakeholder engagement. Testing this qualitative implementation method with a standardised EC assessment tool in other limited resource contexts is the next step to further improve global EC.